Adult Education at Risk: Fronts of Resistance to Neoliberalism - Mark Abendroth (Adult Education Research Conference, 2014)
This paper theorizes from the literature of neoliberalism and adult education. It considers how neoliberal policies have narrowed the scope of adult education while also evaluating how instructors and students can work to restore the broader scope that fostered participatory citizenship.